Peranan Ibrahim Hasan Dalam Memajukan Pantai Barat Selatan Aceh (1986-1993) - Muhammad Nur; Irwan Irwan; Nurul Hayati; Ida Hasanah; Fahmi Arfan (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2023)
This research is qualitative research that looks at Ibrahim's role Hassan in advance area beach west south Aceh on moment he served as Governor of Aceh (1986-1993). Ibrahim Hasan is known as the governor of Aceh who focuses on Aceh's development, both from economic, educational, social, and cultural aspects and other aspects. So, this research can see the role of Ibrahim Hasan in advancing the South West coast of Aceh (1986-1993 ). This research was conducted in libraries in the cities of Banda Aceh and Aceh Besar. This research uses historical and bibliographic methods so that can develop concepts in answering research problems. The results of this research show that, when he served as Governor of Aceh, Ibrahim Hasan played an important role in advancing the southwest coast of Aceh by opening public transportation routes that were previously difficult for people to pass, bridges and building facilities. education by increasing the number of vocational schools.